Role of mitochondrial permeability transition pore in myocardial ischemia-reperfusion injury in rat models with zinc deficiency - LIAN Ting, ZHANG Rui-jun, XIONG Xiao-lan, ZHANG Xiao-ya, YU Tao, ZHANG Shi-zhong (Jichu yixue yu linchuang, 2022)
Objective To investigate whether zinc deficiency may induce myocardial ischemia-reperfusion (I/R) injury through mitochondrial permeability transition pore (mPTP). Methods The zinc-deficient rat model was established by feeding with a zinc-deficient fodder, myocardial I/R injury was induced with isolated rat hearts which were subjected to 30 min of global ischemia followed by 120 min of reperfusion. Left ventricular catheterization was used to detect cardiac function. The lactate dehydrogenase (LDH) was spectrophotometically measured; and 2,3,5-triphenyl-tetrazolium(TTC) staining method was applied to measure the area of myocardial infarction; Mitochondrial swelling induced by calcium was adapted as a method to examine the opening degree of mPTP. Results Rats with zinc deficiency showed an increased myocardial infarct size and LDH release (P＜0.05), which was associated with a decreased recovery rate of left ventricular contractility(P＜0.05). Compared to control rats, mPTP opening reduced in mitochondria of the heart of zinc-deficient rats before ischemia(P＜0.05), but increased significantly after 30 min ischemia (P＜0.05). The myocardial I/R injury in both control and zinc-deficient rats was significantly attenuated by inhibition of mPTP opening(P＜0.01). Conclusions Zinc deficiency may increase the myocardial I/R injury in rats through increase of mPTP opening.